The bilingual reading practices and performance of two Hispanic first graders - López-Velásquez, Angela M.; García, Georgia Earnest (Bilingual Research Journal, 2017)
This qualitative study used a sociocultural lens to examine how two bilingual Hispanic first-grade girls demonstrated bilingual reading practices (i.e., heteroglossia and translanguaging) as they discussed and read texts in Spanish and English. One girl predominantly received school reading instruction in Spanish, while the other received school reading instruction in English. They both participated in Spanish reading at home. The school reading instruction employed Spanish or English versions of Success for All, and emphasized word recognition strategies appropriate for the language of instruction along with meaning-making strategies. In April, the two girls scored mid- to end-of first grade on a curriculum-based reading assessment in the language of instruction. Neither of them received biliteracy instruction. Their reading levels in the instructional language and exposure to the other language appeared to be sufficient for them to develop and demonstrate heteroglossic practices. Bilingual dynamic reading assessments and home reading sessions with a bilingual researcher revealed that both girls utilized bilingual reading practices to discuss and comprehend texts in their non-instructional or alternate language. One of the girls also used bilingual reading practices to discuss texts in the instructional language. To read in the alternate language, they both employed word-recognition and meaning-making strategies, which had been emphasized in their school reading instruction. However, one girl’s attempt to use a decoding strategy she had learned in English (i.e., onset-rime) to decode unfamiliar Spanish words did not work effectively. Implications are delineated for the bilingual reading instruction and assessment of young bilingual children.
Keywords: dept.sed

The challenges of recruiting and retaining dual language teachers - Howard, Elizabeth; López-Velásquez, Angela M. (Dual language education: teaching and leading in two languages, 2019)
Across the United States, the popularity of dual language education (DLE) has grown considerably over the past several decades, but finding qualified bilingual teachers to staff these programs is an ongoing issue for administrators. Using the Guiding Principles for Dual Language Education as a framework, this chapter addresses this urgent issue by exploring dual language teacher recruitment and retention through the experiences and recommendations of teachers and administrators in Connecticut. Findings address participants’ perceptions of teacher recruitment and retention, staff selection, workplace climate, and staff evaluation. Cross-cutting themes include the value of shared responsibility and shared decision-making in addressing this complex issue, the need for creativity and flexibility to increase pathways to certification for dual language teachers, and the importance of positive working conditions.
Keywords: Alternative routes to certification; Bilingual teachers; Dual language; School climate; School-university partnerships; Teacher certification; Teacher recruitment; Teacher retention; Teacher shortage; dept.sed